IMPLEMENTATION OF MARKETING STRATEGY FOR IMPROVING SALES VOLUME (CASE STUDY: SELARAS FASHION TENUN) - Ratu Sakina, Ariendra
Currently the fashion industry developed in Indonesia and become one of the trends that keep followed from young people to adults. In this era that have been advanced with technology, more facilitate a lot of people to easily access the trend of what is going on in the community. Most of them were following the trend and some business is take the opportunity which happened to use the moment at the right time. Selaras is a fashion business concern in tenun fashion including clothing and textiles, he uniqueness of Selaras fashion is the clothes combined with one or more tenun motifs. Selaras become one of the business that follow the current development by introducing the tenun textiles originally made by Indonesia. the lack of Indonesian people aware that Indonesia has a traditional unique textiles that is even attracted by international community. Unfortunately the price of tenun relative expensive that is become one of the consideration people to buy tenun. This has led Selaras is not optimal improving it sales volume.